2020
DOI: 10.3390/met10020196
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Test-Panel Orientation and Exposure Angle on the Corrosion Rate of Carbon Steel. Mathematical Modelling

Abstract: The effects of both test-panel orientation and exposure angle on the atmospheric corrosion rates of carbon steel probes exposed to a marine atmosphere were investigated. Test samples were exposed in a tree-shape metallic frame with either three exposure angles of 30°, 45° and 60° and orientation north-northeast (N-NE), or eight different orientation angles around a circumference. It was found that the experimental corrosion rates of carbon steel decreased for the specimens exposed with greater exposure angles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…(A virtual compass rose generated with the proposed Virtual Twin computation procedure is already added to the figure.) Effects of geographical orientation and inclination angle on the corrosion of steel panels were also reported by Santana et al (2020). Table 1, where corrosion values for aluminum in diverse micro-environments are listed for different geographical orientations, illustrates more complex relationships (Klassen et al, 2002).…”
Section: Corrosionmentioning
confidence: 95%
See 1 more Smart Citation
“…(A virtual compass rose generated with the proposed Virtual Twin computation procedure is already added to the figure.) Effects of geographical orientation and inclination angle on the corrosion of steel panels were also reported by Santana et al (2020). Table 1, where corrosion values for aluminum in diverse micro-environments are listed for different geographical orientations, illustrates more complex relationships (Klassen et al, 2002).…”
Section: Corrosionmentioning
confidence: 95%
“…Effects of local and micro-environmental effects on the corrosion of steel structures were investigated by several authors, whereby the intensity of corrosion was found to depend on geographical location, geographical orientation, inclination angle, and local structural design (e.g. sheltering) (Jeffrey and Melchers, 2008; Klassen et al, 2002; Kühne, 2015; Santana et al, 2020; Slamova et al, 2012); thus on particular reference areas. The importance of the geographical location for the intensity of environmental (corrosive) loads is highlighted in Figure 6, where salinity (world-wide) and wind direction (Europe) above marine locations are mapped (Slamova et al, 2012).…”
Section: Corrosionmentioning
confidence: 99%
“…At present, no mathematical models for C 1 prediction depending on the exposure conditions of metal samples are available. Only Santana et al [35] suggested mathematical models for the prediction of the variation in the corrosion rate ( CR ) of carbon steel for a time of up to 7 years depending on the atmosphere parameters, the angle of inclination of samples (30°, 45° and 90° relative to the horizon) and their orientation relative to the wind orientation (N, NE, E, SE, S, SW, W and NW). Experimental data were obtained in 6 exposures of samples that lasted from 60 to 396 days.…”
Section: Introductionmentioning
confidence: 99%
“…Both works by Santana et al reported on atmospheric corrosion of zinc, copper and carbon steel [12,13]. It was found that the most influential environmental parameter affecting the corrosion rates was the chloride deposition rate (S d ), and on the contrary, the environmental temperature (T) showed the smallest influence.…”
mentioning
confidence: 99%